PENDAMPINGAN PRAKTEK IBADAH PADA MASA PANDEMI COVID-19 BAGI ANAK USIA DINI DI DESA PULAU PADANG KEC.SINGINGI KAB.KUANTAN SINGINGI - Yenni Yunita; Dian Tri Utami; Ary Antoni Putra; Riski Rohima; Dilla Wahyuni Safitri (Kreasi: Jurnal Pengabdian Masyarakat, 2021)
The introduction of worship to children at an early age must be done with love, fun and without elements of coercion. Guidance and habituation of worship starts from the family by both parents and is continued to school in a professionally programmed manner. Worship that is instilled in children from an early age of course begins with simple materials such as prayer, fasting, zakat, hajj and umrah, habituation of daily prayers and so on. The location of this community service is carried out at Harapan Bunda Kindergarten, Pulang Padang Village, Singingi District, Kab. Kuantan Singingi. During the Covid-19 Pandemic, an effort is needed to overcome the problem of limited online and face-to-face learning in providing Worship Practice Assistance for Early Childhood. Where, the role of teachers and parents is very influential in helping facilitate children's learning activities as well as providing motivation and reinforcement to children in learning and worship. The results of this community service include: (1) There is an increase in knowledge and understanding of participants about the procedures for carrying out worship practices for Early Childhood. (2) All participants have understood the procedures for practicing Worship for Early Childhood, including: procedures for ablution, prayer and reading, hajj and umrah. (3) Increased insight to early childhood education teachers related to mentoring worship practices in order to develop Spiritual aspects of early childhood starting from the introduction of Worship Materials and the Demonstration stage starting from planning, implementing and evaluating.